Planktonic eggs and early larvae of the sardine, Sardinella dayi Regan - Bensam, P (Indian Journal of Fisheries, 2011)
The specific identity of the eggs of & Sardinella sp. collected in March 1967 from Tuticorin waters was established as Sardirella dayi on the basis of recent researches on embryonic taxonomy of the sardines. The parameters considered for such specific identification were the diameters of the whole egg, yolk and oil globule. By rearing the eggs up to early postlarval stages and studying the distribution of pigment spots and the number of prearul and postanal myomeres, the identification was further confirmed. The subtle differences with the closely resembling eggs and larvae of S. dayi, S.fimbriata and S. longiceps were also examined